Answer:
y = 5/3
x = 8/3
Steps:
y = x - 1
2x + y = 7
Substitute y = x-1
(2x + x - 1 = 7)
Simplify: 3x - 1 = 7
Isolate x: 3x - 1 = 7: x=8/3
Plug the valuse of x into the other equation (y = x- 1): y = 8/3 - 1
8/3 - 1 = 5/3
y = 5/3
y = 5/3, x = 8/3
Answer:
approximately 9.2195
Step-by-step explanation:
We can use Pythagorean theorem
one leg is 7 and the other leg is 6
square them
49 and 36
add
85
square root
approximately 9.2195
2. 5(x-1)=-3x+35
5x-5=-3x+35
5x=-3x+30
2x=30
x=15
Answer:
It would be the first one or second one
Step-by-step explanation:
the answer is up ahead